Integrated Marketing Communications Implementation of Pegipegi to Boost the Purchase Intention During Pandemic: Studi Kasus pada Kampanye PegipegiLagi - Sheren Valentia; Bangun, Cendera Rizky (LPPM Stikosa - AWS, 2023)
The pandemic has caused people's activities to be limited, then causing negative impacts on various aspects of life, especially the economic aspect of tourism. So, Pegipegi did many marketing activities to survive during the pandemic, one of them was launching the Pegipegilagi campaign. The purpose of conducting this research is to find out, analyze, and understand the Integrated Marketing Communication strategy conducted by Pegipegi Online Travel Agent to encourage buying interest during the pandemic. The concepts used in this research are marketing communication, Integrated Marketing Communication planning process, tools for Integrated Marketing Communication, and purchase intention. This research also uses the case study method with data collection technique by conducting in-depth interviews with four participants and one expert, then equipped with documentation study. The result of this research showed that Pegipegi had implemented Integrated Marketing Communication Planning Process and used 6 Tools for Integrated Marketing Communication by Belch & Belch in conducting IMC activities. The activities of Pegipegi's Integrated Marketing Communication in the PegipegiLagi campaign have succeeded in encouraging the target audience's buying interest, then increasing Pegipegi's transactions during the pandemic.